Dysfunctions of sleep and the circadian rhythm in Huntington’s disease - Kaczmarska, Paulina; Rudzińska-Bar, Monika (Frontiers in Neurology, 2025)
Sleep and circadian rhythm disturbances are highly prevalent in Huntington’s disease (HD) and increasingly well characterized through both subjective assessments—such as questionnaires—and objective techniques, including polysomnography and actigraphy. These disturbances encompass a broad range of features, including sleep fragmentation, altered sleep architecture, insomnia, and delayed circadian phase, often emerging years before motor onset. This review outlines the clinical relevance of sleep dysfunction in HD and its potential bidirectional relationship with neurodegeneration, highlighting mechanisms that may contribute to symptom progression and disease burden. Emerging evidence, primarily from preclinical HD models, suggests that dysregulated sleep–wake and circadian processes may accelerate underlying neuropathological changes. We describe the clinical presentation of sleep-related disturbances in HD, including abnormal nocturnal motor activity and insomnia, while also noting less frequent phenomena such as sleep-related breathing disturbances and REM sleep behavior disorder (RBD). In parallel, we summarize findings on circadian misalignment and its association with altered melatonin signaling, hypothalamic pathology, and disrupted gene expression rhythms. Sleep and circadian disturbances are further linked to cognitive impairment and reduced quality of life. Finally, the review outlines current therapeutic strategies—derived from studies in other neurodegenerative disorders, animal models, and the first randomized controlled trial conducted in HD—highlighting the need for targeted interventions. Altogether, the available evidence suggests that sleep and circadian dysfunctions are modifiable components of HD that warrant greater attention in both research and clinical practice.